Comparison Of Two Hydrological Models (Lumped And Distributed) Over A Pilot Area Of The Issen Watershed In The Souss Basin, Morocco - Hassan Brirhet; Lahcen Benaabidate (European Scientific Journal, ESJ, 2016)
The present study aims to develop a hydrological model of flood forecasting to arid environment in the Issen basin (sub-chatchement of Aguenza basin) through a comparison between two conceptual hydrological models (HEC HMS) and ATHYS which is a conceptual distributed model rarely used in the Moroccan context. The aim is to measure the degree of adaptability of these models to the study area in order to generalize the selected model to the entire watershed. The obtained results from the validation phase of the two models were satisfactory, the two models were able to reproduce the hydrological behavior of the Aguenza watershed during flooding periods. Besides, this study has shown that a good distributed model can provide improvements over a global model for flood forecasting and particularly in terms of volume as in the present study case.